Regulatory Mechanisms of Phytohormones in Thiocyanate-Exposed Rice Plants: Integrating Multi-Omics Profiling with Mathematical Modeling - Yi Kang; Chengzhi Li; Xiaozhang Yu (Life)
Plants experience various abiotic stresses, among which pollutant stress is one of the most damaging, threatening plant productivity and survival. Thiocyanate (SCN−), a recalcitrant byproduct of industrial processes, poses escalating threats to agroecosystems by disrupting plant hormonal homeostasis, which is critical for stress adaptation. Here, we dissect the regulatory interplay of phytohormones in rice (Oryza sativa L.) under SCN− stress (4.80–124.0 mg SCN/L) through integrated transcriptomic and metabolomic profiling. Quantitative hormonal assays revealed dose- and tissue-specific perturbations in phytohormone homeostasis, with shoots exhibiting higher sensitivity than roots. Transcriptomic analysis revealed that a number of differentially expressed genes (DEGs) mapped in different phytohormone pathways in SCN−-treated rice seedlings, and their transcript abundances are tissue-specific. To identify the phytohormones governing rice’s sensitivity to SCN− stress, we developed a Total Hormonal Sensitivity Index (THSI) through an integrative multivariate framework, which combines Modified Variable Importance in Projection (VIP(m)) scores to quantify hormonal fluctuations and Total Weighted Contribution Scores (TWCS) at the gene-level from hormonal pathways. This study establishes a system-level understanding of how phytohormonal crosstalk mediates rice’s adaptation to SCN− stress, providing biomarkers for phytoremediation strategies in contaminated paddies.